Latin American identity in online cultural production - Taylor, Claire, 1972- (Routledge studies in new media and cyberculture ;, 2013)
"This volume provides an innovative and timely approach to a fast growing, yet still under-studied field in Latin American cultural production: cyberculture. It focuses on the transformations or continuations that cultural products and practices such as hypermedia fictions, net.art and online performance art, as well as blogs, films, databases and other genre-defying web-based projects, perform with respect to Latin American(ist) discourses, as well as their often contestatory positioning with respect to Western hegemonic discourses as they circulate in cyberspace. The intellectual rationale for the volume is located at the crossroads of two, equally important, theoretical strands: theorizations of cyberculture, in their majority the product of the anglophone academy; and contemporary debates on Latin American identity and culture. "--